Human herpesvirus replication and abnormal CD8+ T cell activation and low CD4+ T cell counts in antiretroviral-suppressed HIV-infected patients. - Mark A Jacobson; Dirk P Ditmer; Elizabeth Sinclair; Jeffrey N Martin; Steven G Deeks; Peter Hunt; Edward S Mocarski; Caroline Shiboski (PLoS ONE)
Background Most HIV-infected patients receiving virologically suppressive antiretroviral therapy continue to have abnormal, generalized T cell activation. We explored whether the degree of ongoing cytomegalovirus (CMV), Epstein-Barr virus (EBV) and Kaposi's sarcoma herpesvirus (KSHV) replication was associated with higher virus-specific T cell activation and the failure to achieve normal absolute CD4+ T cell counts in the face of long-term suppressive antiretroviral therapy. Methodology Longitudinally collected PBMC and saliva specimens obtained from HIV-infected patients on effective antiretroviral therapy for at least one year (plasma HIV RNA <75 copies/mL) were examined using a multiplex CMV, EBV and KSHV DNA PCR assay. Eleven cases were chosen who had CD8+ T cell CD38+HLA-DR+ expression >10% and plateau absolute CD4+ T cell counts <500 cells/microL. Five controls from the same study had CD8+ T cell CD38 expression <10% and plateau absolute CD4+ T cell counts >500 cells/microL. Results and conclusions Among all subjects combined, 18% of PMBC samples were positive for CMV DNA, and 27%, 73% and 24% of saliva samples were positive for CMV, EBV and KSHV DNA, respectively. No significant differences or trends were observed between cases and controls in proportions of all CMV, EBV or KSHV DNA positive specimens, proportions of subjects in each group that intermittently or continuously shed CMV, EBV or KSHV DNA in saliva, or the median number of genome copies of CMV, EBV and KSHV DNA in saliva. Overall, number of genome copies in saliva were lower for KSHV than for CMV and lower for CMV than for EBV. Although replication of CMV, EBV and KSHV persists in many antiretroviral-suppressed, HIV-infected patients, we observed no evidence in this pilot case-control study that the magnitude of such human herpesvirus replication is associated with abnormally increased CD8+ T cell activation and sub-normal plateau absolute CD4+ T cell counts following virologically suppressive antiretroviral therapy.